Differences in the Effectiveness of Giving Dark Chocolate and Ginger to Reducing Menstrual Pain Intensity in SMAN 1 Cikande Students in 2022 - Puji Dwi Astutik; Achmad Fauzi (STIKep PPNI Jawa Barat, 2022)
Aims: Menstrual pain (dysmenorrhea) is pain during menstruation that is usually experienced by young women with complaints of aches or cramps in the lower abdomen and pelvis. Menstrual pain (dysmenorrhea) often begins after the first menstruation. Pain decreases after menstruation, but pain can continue to be experienced during menstrual periods in some women so that it has an impact on daily activities, such as school activities and work. Objective: This study aims to analyze differences in the effectiveness of giving dark chocolate and ginger to reduce the intensity of menstrual pain in female students at SMAN 1 Cikande. Methods: In this study, the researcher used a Quasi Experimental Pre-Posttest with Control Group design. The population in this study were all female students who experienced menstrual pain during menstruation. 28 female students with a sampling technique using the Non-Probability Sampling technique or Non-Random Sampling with the Purposive Sampling method. Result: The results of the study were differences in the intensity of menstrual pain reduction with the non-parametric test, namely Wilcoxon in 14 respondents who were given dark chocolate with a p-value of 0.001 < (0.05) while 14 other respondents who were given ginger a p-value of 0.001 < (0 0.05 Differences in the effectiveness of dark chocolate and ginger based on the Mann Whitney test p-value 0.299 > (0.05). Conclusions and Suggestions: There was no significant difference in the effectiveness of reducing pain intensity in students of SMAN 1 Cikande Serang Regency between those given dark chocolate and ginger for 3 days of treatment. It is hoped that non-pharmacological interventions can be applied to treat menstrual pain.